Islamic Acculturation In The Ancestors’ Legacy Of Nanga Suhaid Village, West Kalimantan - Bibi Suprianto (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2020)
This paper attemps to describe how Islamic acculturation was formed in the tradition of Nanga Suhaid Village, West Kalimantan. This paper shed light on community activities in relation to religious interactions, especially in the inner part of the West Kalimantan region, namely Suhaid Sub-district Nanga Suhaid village, Kapuas Hulu district. This study utilized observation, interview, and documentation for data collection through the lens of an anthropological perspective. The results of the study showed: 1) practice of the tradition in the Suhaid village that has long been carried out is a means to maintain the existing traditions. 2) the expression of Islamic Da’wah values could be seen from